A comparative case study of the strategic internet communication of one local and one international contemporary organisation - Getkate, Grant (The IIE, 2017)
The following study was a comparative case study of the strategic internet communication of one local and one international contemporary organisation. The study was conducted in order to assess the strategic online communication of two organisations operating in retail, in different regions. The study sought to evaluate the ways in which the respective organisations seemingly wished to position themselves towards stakeholders and shareholders of the organisations. The population of the study involved any form of strategic internet-based communication produced by, or about, the chosen organisations. The data collection method for the study was that of desk research, a form of secondary research. Data analysis was conducted by means of content analysis. Interpreted findings noted that both organisations similarly communicated their consumer/customer consideration, their environmental and social consciousness in stated procedures and policies as well as their proud traditions, growth and market leadership. The study aimed to contribute to the strategic organisational communication body of knowledge by employing a comparative case study for structuration of findings. Positioning theory was applied as a theoretical framework through which to view the data and underpin findings. Future studies may seek to combine the use of case studies and positioning theory to analyse strategic communication.
Keywords: Organisational communication; Internet communication; Strategic communication